Students’ English Lesson Attitudes and Its Effects on their English Achievement - Wiwaharini, Yuditha Putri (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2019)
This research is aimed to analyze students’ English lesson attitude and its effect on their English achievement. This research is a pre-experimental and it was carried out at one joint-cooperation school in Surabaya, Indonesia. Since English is the language that mostly used at the joint-cooperation school, the parents that sent their children there must have high expectations of their children’s English ability. This pressure can affect the students in learning English in the class. Some students will have negative attitudes in learning English because their parents do not want them to fail. Therefore, the researcher took a sample of 17 students in grade 3 as her subjects. The writer used a questionnaire to measure students’ attitude towards English lesson and compare it with students’ English score. The result shows that students’ attitudes do affect their English achievement. Those students who have positive attitudes towards English will stimulate their mood to absorb the information better.